A direct role of RNA polymerase III and RNA in DNA homologous recombination. (4th July 2021) - Liu, Sijie; Kong, Daochun
ABSTRACT: End resection excises several thousand bases from the 5ʹ-ended strand during DNA double-strand break repair, creating 3ʹ-end single-stranded DNA overhangs. This overhang requires strict protection from DNA2 or other nucleases digestion. A recent finding showed that the 3ʹ-end overhangs are protected by the transient formation of RNA-DNA hybrids, and RNA polymerase III is an essential factor for homologous recombination.